1979
DOI: 10.2135/cropsci1979.0011183x001900030020x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability for Cell Wall Constituents and Associated Quality Traits in Reed Canarygrass1

Abstract: Forage dry matter intake potential by ruminants is negatively associated with its cell wall constituent (CWC) concentration. The objectives of this study were to estimate genetic variance components and determine combining ability and heritability of CWC percent, and other associated quality traits in reed canarygrass (Phalaris arundinacea L.). Genotypic correlations were computed between paired characters. Twelve heterozygous clones used in two 6 ✕ 6 diallels and progenies from 30 crosses were grown for 2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…The highly consistent and positive genetic correlation between NDF and forage yield in Years 1 and 2 is consistent with numerous previous studies (Casler, 1999; Han et al, 2001; Hovin et al, 1976; Marum et al, 1979; Surprenant et al, 1988). Across harvests, locations, and years, NDF concentration averaged 477 to 687 g kg −1 , averaging 593 g kg −1 for the entire study (Casler, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highly consistent and positive genetic correlation between NDF and forage yield in Years 1 and 2 is consistent with numerous previous studies (Casler, 1999; Han et al, 2001; Hovin et al, 1976; Marum et al, 1979; Surprenant et al, 1988). Across harvests, locations, and years, NDF concentration averaged 477 to 687 g kg −1 , averaging 593 g kg −1 for the entire study (Casler, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study suggest that these solutions are unlikely to result in large changes to the natural genetic correlation between NDF concentration and forage yield. Previous estimates of this genetic correlation range from 0.53 to 0.89 (Casler et al, 1990; Hovin et al, 1976; Marum et al, 1979) and these results suggest that this genetic correlation is not likely malleable by selection.…”
Section: Discussionmentioning
confidence: 56%
“…2-6 NIR reflectance spectroscopy was used to measure forage quality in genetics and breeding programmes. 7 This method even allows the efficient determination of organic matter digestibility of grass, hay or silage. 8,9 The key step for using NIR spectroscopy as an analytical technique for forage analysis is the compilation of a wide spectral library.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have reported small negative correlations between yield and digestibility (e.g. Carlson et al, 1969;Hovin et al, 1976;Hill and Barnes, 1977;Marum et al, 1979;Tan and Tan, 1982). Others have reported little or no correlation between DMD and yield (Vogel et al, 1981;Ehlke et al, 1983).…”
Section: Grassesmentioning
confidence: 99%